ARANSEMEN LAGU NYAMANLAH JIWAKU KARYA PHILIP PAUL BLISS DALAM FORMAT QUARTED GITAR - Andreas; Jonathan (Universitas Kristen Immanuel, 2024)
The arrangement is a rewriting work of an existing composition with the addition of new material or the completion of the design of a composition.Based on the observation of the musical works, rarely people who play and arranged a song“It Is Well With My Soul” using a guitar instrument in a quartet format. Many other formats play the arrangement of this song, played in pianos, strings, choirs, guitar solos, and orchestras, and in a quartet guitar format is rarely played, that is the reason researchers interested conduct this research. It is well with my soul is a song from Hymn of praise, the lyrics of this song were created based on Horatio G Spafford (1828) experience.Whose then melody was created by Phillip Paul Bliss (1838) was a leader of compliments and composers from America. Philip was impressed by the lyrics that had been written by spafford. And then philip created a melody based on his life experience, that song called “it is well with my soul”.To arranged a song we must understand about melody, harmony, interval, rhythm, musical form, and instrument character to be used in the arrangement of songs that we will arrange to become a new arrangement. Before arranging a song we must choose the music format to be used, In this arrangement will use Quartet guitar format as a musical instrument to play the song arrangement, The guitar quartet is a category of similar ensembles using classical guitar instruments and played by four guitar players. In the methodology of creation there are three stages before we arranged a song. The first stage is to create the idea of making arrangements, the second stage is to design the arrangement of songs, the third stage is the implementation, displaying the work of the arrangement. Overall from this arrangement that have been made, there is something unique, that the original melody is not always on the first guitar, but also played by other guitar players, to change the outgoing sound dimension when played. In the new arrangement the song is divided into three variations, Variation I starts from the bar 31-46, Variation II is starts from the bar 56-97 and Variation III starts from the bar 98-147.